Cardiac disease and prognosis associated with ventricular tachyarrhythmias in young adults and adults - Weidner, Kathrin; Behnes, Michael; Schupp, Tobias; Hoppner, Jorge; El-Battrawy, Ibrahim; Ansari, Uzair; Saleh, Ahmad; Taton, Gabriel; Reiser, Linda; Kern-Bollow, Armin; Reichelt, Thomas; Ellguth, Dominik; et al. (BMC cardiovascular disorders, 2022)
This study evaluates cardiac diseases and prognosis in young adults and adults presenting with ventricular tachyarrhythmias (VTA).
Published: 31 March 2022
Gesehen am 26.09.2022